Determinants of sustainability reporting in medium enterprises - Paiva, I. S.; Gavancha, I. F. (Maintaining Sustainable Accounting Systems in Small Business, 2018)
The importance of the relationship between sustainability and accountability in the business world has increased in the last few years. This chapter examines the determinants of sustainability reporting in 100 medium enterprises operating in Portugal with an excellent financial performance over the past three years. The main results demonstrate that firm characteristics, such as size, ownership structure, and sales growth, contribute significantly to explaining sustainability in these firms. The authors also find that medium firms exhibit a lack of interest in changing their business conduct to improve sustainability. Sustainability accounting is in a relatively early phase of development and the authors hope that this study will further the understanding of the firm characteristics that explain sustainability in medium enterprises.